PENDAMPINGAN PENILAIAN KINERJA USAHA KERAJINAN DI PINANG KOTA TANGERANG - Arifin Djaka Saputra; Ardiansyah Ardiansyah; Maswar Abdi Abdi (Jurnal Bakti Masyarakat Indonesia, 2021)
The objective of the activity is to provide assistance to recycling handicraft businesses in Tangerang in assessing business performance. Through provision of knowledge on how to assess business performance and assistance in assessing the performance of businesses that have been running so far. This activity refers to the results of the research grant from the Directorate General of Higher Education as a team member, regarding the IKM business performance appraisal instrument is very necessary in running a business. in order to build a competitive advantage. The activity is carried out at the Lumintu business group, which employs the elderly to make plaits in Sudimara Pinang, Tangerang City. Based on the analysis of partner problems, there is still weak knowledge of performance appraisals so that they have not been able to achieve competitive advantage. The method offered in this activity is to implement a performance appraisal instrument in the form of socialization and assistance to Lumintu business owners. Through socialization about performance appraisal. Partners are very enthusiastic in listening to the material that has been delivered, and there is two-way communication between partners and the team. Furthermore, the assistance assesses the performance. Overall, the business performance is considered adequate. There are several things that need to be improved, such as the internal performance in the aspect of human resources and finansial.It is quite difficult for partners to retain the elderly to continue making weaving. For that we need continuous motivation to remain productive. ABSTRAK:Tujuan kegiatan adalah melakukan pendampingan pada usaha kerajinan daur ulang di Tangerang dalam menilai kinerja usaha. Melalui pembekalan pengetahuan tentang cara menilai kinerja usaha dan pendampingan menilai kinerja usaha yang selama ini telah dijalankan. Kegiatan ini mengacu dari hasil penelitian hibah dikti sebagai anggota tim, tentang instrumen penilaian kinerja usaha IKM sangatlah diperlukan dalam menjalankan usaha. agar dapat membangun keunggulan bersaing. Kegiatan dilakukan pada kelompok usaha Lumintu yang memperkerjakan para lansia membuat anyaman di Sudimara Pinang Kota Tangerang. Bedasarkan analisis masalah mitra , masih lemahnya pengetahuan akan penilaian kinerja sehingga belum mampu mencapai keunggulan bersaing. Metode yang ditawarkan pada kegiatan ini adalah mengimplementasikan instrumen penilaian kinerja dalam bentuk sosialisasi dan pendampingan kepada pemilik usaha Lumintu. Melalui sosialisasi tentang penilaian kinerja. Mitra sangat antusias dalam mendengarkan materi yang telah disampaikan, dan terjadinya komunikasi dua arah antara mitra dengan tim. Selanjutnya pendampingan menilai kinerja. Secara keseluruhan kinerja usaha dinilai cukup. Ada beberapa hal yang harus diperbaiki seperti pada kinerja internal di aspek SDM dan keuangan. Cukup sulit bagi mitra mempertahankan para lansia untuk terus lanjut membuat anyaman. Untuk itu perlu motivasi secara terus menerus untuk tetap menjadi produktif